2018
DOI: 10.5513/jcea01/19.3.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tytanit on the dry matter and macroelement contents in potato tuber

Abstract: This paper analyses the effect of the dose (0.2 L*ha-1 or 0.4 L*ha-1) and date (a single application at the leaf development stage-BBCH 14-16 or at the tuber formation stage-BBCH 41-43, and a double application at the BBCH 14-16 and BBCH 41-43 stages) of the application of Tytanit ® (8.5 g Ti per liter in the form of Ti-ascorbate) on the dry matter and macroelement contents in tuber of very early potato cultivars ('Lord' and 'Miłek'). Potatoes were harvested 75 days after planting (the end of June). Tytanit ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…A previous study showed that the soil reaction affects the mass ratio of Ca:P in potato tubers [40,42], which was confirmed in the present study. Regardless of treatment (with or without biostimulant), the Ca:P ratio was narrowest and the K + :Ca 2+ and Na + :Ca 2+ ratios were broadest in the potato tubers from the soil with lowest pH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A previous study showed that the soil reaction affects the mass ratio of Ca:P in potato tubers [40,42], which was confirmed in the present study. Regardless of treatment (with or without biostimulant), the Ca:P ratio was narrowest and the K + :Ca 2+ and Na + :Ca 2+ ratios were broadest in the potato tubers from the soil with lowest pH.…”
Section: Discussionsupporting
confidence: 91%
“…Nutrient uptake by plants depends on their phytoavailability in the soil and on their synergism and antagonism interaction [40,41]. There is limited information about the effect of biostimulants on the macronutrient ionic ratios in potato tubers [42]. The biostimulants used in the experiment caused an increase in the mass ratios of K + :Ca 2+ and K + :Mg 2+ in potato tubers, as a result of an increase of K content, compared to the untreated control tubers, but did not affect the mass ratios of Na + :Ca 2+ and Na + :Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…The above authors recorded a widening ratio of those cations in consecutive growing periods, and this trend was confirmed in the present experiment. Different results were provided by Wadas and Kalinowski (2018) , in whose experiment Tytanit foliar application did not contribute to changes of calcium and phosphorus accumulation in potato tubers, leading to no diversification of their ratio.…”
Section: Discussionmentioning
confidence: 82%
“…A great variety of biostimulant products with different active compounds have been suggested for application in the agricultural sector, including phenolic acids [195], triglycerides [196], titanium [2,197], or zeatin from Moringa oleifera leaves [198]. Moreover, chitosan is another important biopolymer with biostimulant activities which has been used to alleviate water stress negative effects and increase shelf life on horticultural crops such as basil [92], lettuce [71], spinach [72], tomato [183], and pepper [184], among others.…”
Section: Practical Applications Of Biostimulants and Biostimulatory Products On Horticultural Cropsmentioning
confidence: 99%